Community analysis of large epibenthos in the Nordic Seas - Dos Santos, Eric Ruben, 1972- (2010)
The aim of the presented project was to provide information about the community structure and diversity of epibenthic megafauna in the Nordic Seas. The focus was the importance of hard substrate in the formation and definition of animal communities. The study was based on photographs from the Greenland-Iceland-Faeroes Ridge (GIF) and photographs and videos collected from the Jan Mayen Fracture Zone (JMFZ) and the Mohn Ridge. The GIF samples were collected from eight stations to the northwest of Iceland using a frame-mounted camera. Videos and stills collected from the JMFZ and the Mohn Ridge were recorded using an ROV. All animals large enough (>1 cm diameter for photographs, >5 cm diameter for videos) were identified to lowest possible taxonomic level. On the GIF Ridge, community structure was found to vary somewhat between stations but also, within stations. Community structure was more strongly influenced by high habitat heterogeneity than by other measured environmental variables. The presence of hard surfaces in soft sediment areas caused a shift of community structure from that found on soft bottoms to one more like that found on hard bottoms. The wider scope provided by video data from the JMFZ and Mohn Ridge areas showed distribution of epifauna in patches where high dominance of a few taxa was observed. This patchiness seems to be the result of presence or absence of hard surfaces to act as anchor sites for sessile and semi-sessile species.